STRATEGI BRANDING UNTUK MEMBANGUN IMAGE POSITIF PANGAN LOKAL BAGI USAHA MIKRO KECIL DAN MENENGAH - Dyah Panuntun Utami (Journal of Food Technology and Agroindustry, 2021)
Indonesia has many types of local food with their own uniqueness. This potential has not been matched by people's interest in consuming local food. This is due to the low level of food processing technology innovation to produce prestigious local food. Micro small and medium enterprises are also low in building product image. Building a positive image of local food requires a study to obtain the right branding concept. The study method uses a post positivistic paradigm and inductive thinking patterns. The result of this study is that the branding strategy is focused on product branding. Building a positive image of local food is done by improving the physical appearance of the product by processing innovation, improving packaging, labeling, and paying attention to consumer tastes, then communicating intensively to the public. The branding concept is made simple, hits the hearts of the public, and must be consistent in maintaining the value of the product. Micro, small and medium enterprises must be diligent and creative in finding ideas to maintain consumer loyalty.